Obtenção de filmes finos de TiO2 nanoestruturado pelo método dos precursores poliméricos - Stroppa, Daniel Grando; Giraldi, Tania Regina; Leite, Edson Roberto; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Sociedade Brasileira de Química, 2008)
This work focuses in optimizing setup for obtaining TiO2 thin films by polymeric precursor route due to its advantages on stoichiometric and morphological control. Precursor stoichiometry, synthesis pH, solids concentration and rotation speed at deposition were optimized evaluating thin films morphology and thickness. Thermogravimetry and RMN were applied for precursor's characterization and AFM, XRD and ellipsometry for thin films evaluation. Results showed successful attainment of homogeneous nanocrystalline anatase TiO2 thin films with outstanding control over morphological characteristics, mean grain size of 17 nm, packing densities between 57 and 75%, estimated surface areas of 90 m²/g and monolayers thickness within 20 and 128 nm.
Nanostructured TiO2 thin films by polymeric precursor method
Keywords: titanium dioxide; thin films; polymeric precursor